Penggunaan Media Loose Part untuk Mengembangkan Kreativitas Anak Usia Dini di KB ’Aisyiyah Ar Rozan Kabupaten Wonosobo - Fela Faridati Rizkiyani; Desti Pujiati Pujiati (UM Purwokerto Press, 2026)
This study aims to investigate whether the use of loose parts media can enhance creativity in early childhood at KB ‘Aisyiyah Ar Rozan, Wonosobo regency. The background of the study steam from learning practices that remain heavily reliant on textbooks and printed teaching materials,which do not sufficiently encourage children’s creativity. Instructional media should serve as a tool to support creative development activities and stimulate children’s interest in the learning process. This study employed a collaborative Classroom Action Research (CAR) method using the spiral model by Kemmis and Mc Taggart, which includes systematic stages such as planning, action implementation, observation, reflection, and re-planning to address educational challenges effectively. The findings, based on observation of 15 children, revealed that 12 children (or 80%) showed improved creativity categorized as “very Well Developed” (VWD). The gradual and enjoyable use of loose parts media proved effective in stimulating early childhood creativity. Childrens creativity can flourish when they are provided with the right stimuli and are continuously encouraged through various creative exercises. Learning through loose parts media allows children to be more active, confident, joyful, expressive, and less prone to boredom. Loose parts refer to open-ended materials that can be arranged, separated, or combined with other objects to create a product or artwork. These materials may include metal, plastic, wood, or other components. The use of this media provides children with the freedom to explore, fosters curiosity, develops imagination, and cultivates an appreciation for beauty.